International migration and movement of nursing personnel to and within OECD countries - 2000 to 2018 Developments in countries of destination and impact on countries of origin - Socha-Dietrich, Karolina (OECD Health Working Papers, 2021)
This paper presents the most recent data on the extent to which migrant nurses contribute to the nursing workforce in the OECD countries as well as the impact these regular migration flows have on the countries of origin, including an analysis of the developments since 2000. The objective of this paper is to provide new data for policy dialogue at the national and international levels. The shares of foreign-born or foreign-trained nurses have continued to rise over the last two decades across the OECD countries, with intra-OECD migration making up a third of the migration volume. Regarding the impact on countries of origin, emigration rates to OECD countries are generally moderate but a few countries experience significant losses of (needed) nurses. However, for a significant share of the foreign-trained nurses, the data sources do not allow the identification of the country of training. Hence, some of the results should be treated as lower-bound estimates